HYDRATED SUBDUCTED CRUST AT 100-250 KM DEPTH - Abers G.A. (My University, 2000)
Seismic waves that travel along the surface of subducted slabs provide a means to infer petrology to considerable depth. At high frequencies (0.5-10 Hz) they are particularly sensitive to the presence and state of subducted oceanic crust. New observations reveal systematic distortion of body waves in all north Pacific subduction zones, when signals traverse slabs at 100-250 km depths, suggesting that crust remains distinct to these depths. The signals show waveguide behavior at the scale of a few kilometers: short-wavelength, high-frequency energy (=<3 Hz) is delayed 5-7% relative to that of low frequencies (=<1 Hz), systematically at all subduction zones. To explain these observations, velocities in a low-velocity layer 1-7 km thick, likely subducted crust, must remain seismically slow relative to surrounding mantle at these depths. Hence, it seems unlikely that subducted crust has completely converted to eclogite, as often assumed. Inferred velocities within subducted crust are similar to those estimated for blueschists, suggesting that hydrous assemblages persist past the volcanic front.
Keywords: SUBDUCTION; OCEANIC CRUST; WAVE DISPERSION; METAMORPHISM; VELOCITY STRUCTURE